Clonal and plasmidic dissemination of critical antimicrobial resistance genes through clinically relevant ExPEC and APEC-like lineages (ST) in the dairy cattle population of Québec, Canada - de Lagarde, Maud; Fairbrother, John Morris; Archambault, Marie; Dufour, Simon; Francoz, David; Massé, Jonathan; Lardé, Hélène; Aenishaenslin, Cécile; Paradis, Marie-Eve; Terrat, Yves; Roy, Jean-Philippe (Frontiers in Microbiology, 2024)
Antimicrobial resistance can be effectively limited by improving the judicious use of antimicrobials in food production. However, its effect on the spread of AMR genes in animal populations is not well described. In the province of Québec, Canada, a new legislation implemented in 2019 has led to an unprecedented reduction in the use of critical antimicrobials in dairy production.We aimed to investigate the potential link between ESBL/AmpC E. coli isolated before and after legislation and to determine the presence of plasmids carrying genes responsible for critical AMR.We collected fecal samples from calves, cows, and manure pit from 87 Québec dairy farms approximately two years before and two years after the legislation came into effect. The whole genomes of 183 presumptive ESBL/AmpC E. coli isolated after cefotaxime enrichment were sequenced. Their phylogenetic characteristics (MLST, serogroup, cgMLST) and the presence of virulence and resistance genes and replicons were examined. A maximum likelihood phylogenetic tree was constructed based on single nucleotide polymorphism (SNPs).We identified 10 clonal lineages (same cgMLST) and 7 clones (SNPs ≤ 52). Isolates belonging to these clones could be found on different farms before and after the legislation, strongly suggesting a clonal spread of AMR genes in the population during this 4-year period. All isolates were multidrug resistant (MDR), with clone 2 being notable for the presence of macrolide, fluoroquinolone, and third-generation cephalosporin resistance genes. We also identified clinically relevant ExPEC (ST10) and APEC-like lineages (ST117, ST58, ST88) associated with the presence of ExPEC and APEC virulence genes, respectively. Our data also suggests the presence of one epidemic plasmid belonging to the IncY incompatibility group and carrying qnrs1 and blaCTX-M-15.We demonstrated that AMR genes spread through farms and can persist over a 4-year period in the dairy cattle population through both plasmids and E. coli clones, despite the restriction of critical antimicrobial use. MDR ExPEC and APEC-like STs are present in the normal microbiota of cattle (more frequently in calves). These data increase our knowledge on gene dissemination dynamics and highlight the fact that biosecurity measures should be enhanced in this industry to limit such dissemination.